Bottomonium at Non-zero Temperature from Lattice Non-relativistic QCD - Gert Aarts (PANIC proceedings, 2011)
G. Aarts, C. Allton, S. Kim, M.P. Lombardo, M.B. Oktay, S.M. Ryan, D.K. Sinclair, J.-I. Skullerud, PANIC proceedings, arXiv:1109.1475, 2011